2019
DOI: 10.1159/000504321
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Toll-Like Receptor 3 Induces Interleukin-1 Receptor Antagonist Expression by Activating the Interferon Regulatory Factor 3

Abstract: Toll-like receptor 3 (TLR3) is a sensor of endogenous cell necrosis during the process of acute inflammation. Interleukin (IL)-1 receptor antagonist (IL-1Ra) is an anti-inflammatory cytokine and can negatively regulate the pathogenesis of inflammation. However, whether and how activation of TLR3 can regulate IL-1Ra expression has not been clarified. Here, we show that poly(I:C) induces IL-1Ra expression in primarily cultured human fibroblast-like synoviocytes and other types of cells. Induction of IL-1Ra by po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 54 publications
1
16
0
1
Order By: Relevance
“…30) Moreover, TNF-α is able to upregulate crucial integrins and adhesion molecules on vascular endothelium, including E-selectin and vascular cell adhesion molecule-1 (VCAM-1), which can promote the production of more chemokines to enhance inflammation. 40) Interestingly, some studies have reported that TNF-α can regulate anti-inflammatory mediator interleukin-1Ra (IL-1Ra) in vitro, 41,42) signifying a complicated role TNF-α plays in the development of inflammation. 43) TNF-α also reduces the production of stromal cell-derived factor-1 (SDF-1) in rats, 25) which can induce neutrophil migration and attract leukocytes from the blood into the inflamed tissue.…”
Section: Tnf-α Is Associated With Inflammation In Tmdmentioning
confidence: 99%
See 1 more Smart Citation
“…30) Moreover, TNF-α is able to upregulate crucial integrins and adhesion molecules on vascular endothelium, including E-selectin and vascular cell adhesion molecule-1 (VCAM-1), which can promote the production of more chemokines to enhance inflammation. 40) Interestingly, some studies have reported that TNF-α can regulate anti-inflammatory mediator interleukin-1Ra (IL-1Ra) in vitro, 41,42) signifying a complicated role TNF-α plays in the development of inflammation. 43) TNF-α also reduces the production of stromal cell-derived factor-1 (SDF-1) in rats, 25) which can induce neutrophil migration and attract leukocytes from the blood into the inflamed tissue.…”
Section: Tnf-α Is Associated With Inflammation In Tmdmentioning
confidence: 99%
“…SDF-1 (stromal cell-derived factor-1) 25) NF-κB Induces the neutrophil migration In vitro & in vivo Attracts leukocytes from the blood into the inflamed tissue IL-1Ra (Interleukin-1Ra) 41,42) NF-κB Inhibits the inflammation and connective tissue degradation In vitro TLR4: toll-like receptor 4; MyD88: myeloid differentiation factor; NF-κB B: nuclear factor-kappa B; p38 MAPK: p38 mitogen-activated protein kinase; JNK: Janus Kinase; ERK: extracellular signal-regulated kinases; JAK2: Janus kinase 2; PI3K/Akt: phosphatidylinositol-3 kinase/protein kinase B. TMJ. 45) Simultaneously, mandibular condylar cartilage of the human patients was degraded excessively.…”
Section: In Vitromentioning
confidence: 99%
“…It has been shown that CpG‐DNA–mediated activation of TLR9 not only increased the expression of Bax but also induced caspase‐dependent apoptotic cell death in murine macrophages 75 . Moreover, the interaction of TLR3 with dsRNA triggers a cascade to activate a wide range of downstream axes, such as p38, JNK and IFN regulatory factors, which in turn regulate apoptosis in cancer cells 76 . TLR3‐poly I:C interaction also enhances the therapeutic value of the conventional antitumour agent cycloheximide in different human and murine tumour cell lines through increasing the production of IFN‐γ, a well‐known cytokine which its association with caspase and p53 has been previously well‐established 77 …”
Section: Tlrs In Cancer: Double‐edged Swordsmentioning
confidence: 99%
“…However, also innate immunity plays important roles in mounting protection against viral infections. For instance, it was recently reported that Tollip, a negative immune regulator, can inhibit the proinflammatory response to rhinovirus infection [1], that toll-like receptor 3 can induce interleukin (IL)-1 receptor antagonist expression leading to an induction of anti-inflammatory reactions [2], and that gender-specific hormones such as 17β-estradiol can modulate the innate immune response to viral infections [3]. In addition, we also published that interferons are crucial players in the fight against viral infections as they enhance the innate immune response against many viral pathogens [4-6].…”
mentioning
confidence: 99%